Development of a Biology Virtual Laboratory (V-Lab) for Microscopic Observations about Onion Cells and Cassava Plant Cells - Laili Rahmi; Nidia Zuhara (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research aims to develop a virtual laboratory (v-lab) using Adobe Animate cc 2023 with a project-based evaluation to help students get to know microscopes and understand the steps of their use, especially observe about onion cells and cassava plant cells. This research also aims to evaluate the V-Lab which was developed through validation by validators and effectiveness test by respondents to produce valid, practical and effective media for Biology learning. The research method use Research and Development (R & D) from the 4D model. Data were obtained using a questionnaire given to several validators and respondents amount 39 students. Data analysis was conducted quantitative by calculating the percentage of assessments from validators and respondents and then qualitative analysis with describe the assessment result with validation criteria. The validation results from material experts show that the substance of the material in this V-Lab has been explained with the right concept, easy to understand and systematic. The validation results from media experts show that this media has clear and interested display and navigation with consistent functions.The results of the trial on students showed a higher response to the usability aspect, which means that the media developed can provide knowledge and understanding to get to know microscopes, provide experience as if they were using a real microscope and the use of this V-lab can overcome the limited availability of microscopes in practical activities. The validity of the material and the V-lab media developed makes this media very suitable and interesting to use in biology learning, especially in getting to know microscopes and making simple observations about cells. The limitations of microscope units in the laboratory is no longer a problem to realizing effective learning.